Scarcity mindset in reproductive health decision making: a qualitative study from rural Malawi. Issue 12 (2nd December 2019) - Norris, Alison H.; Rao, Nisha; Huber-Krum, Sarah; Garver, Sarah; Chemey, Elly; Norris Turner, Abigail
Abstract: Poverty has widespread impacts on health. In dealing with resource scarcity, individuals' thoughts are narrowed to address immediate resource limitations, thus crowding out other information, a phenomenon called the scarcity mindset. To assess for indication of a scarcity mindset in sexual and reproductive decision making in rural Malawi, a setting with extreme resource scarcity, we collected qualitative data in the form of eight focus group discussions and 28 semi-structured, in-depth interviews with women and men of varying ages and marital status. Participants, who were of low socioeconomic status, described constant tradeoffs that they made to secure their daily needs. They articulated both the challenges of supporting many children and the need to bear many children to guarantee their own future support. While participants described wealthy people as being concerned with preserving resources (often through the practice of limiting childbearing), they described poor people as working to increase their probability of success against an uncertain economic future (without due consideration of contraceptive behaviours). We found qualitative evidence that a scarcity mindset may influence reproductive decision making among women and men in rural Malawi and may preclude the use of contraception in low-resource settings.